Pengelolaan Media Sosial Youtube Badan Pendapatan Daerah Jawa Barat Sebagai Media Informasi dan Publikasi - Akbar, Zidan Addinul (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
Public Relations of the West Java Bapenda actively uploads information regarding its programs, activities and policies, such as the activities of the Head of the West Java Bapenda, information regarding paying motor vehicle taxes, and also information regarding other services or programs involving the West Java Regional Revenue Agency. The concept used is The Circular Model of Some for Social Communication from Regina Luttrell. This research uses a constructivist paradigm with a qualitative approach and qualitative descriptive methods. Research data was collected through in-depth interviews and observations. This research aims to find out how the process of managing YouTube social media @BapendaJabar as information and publication starts from managing (share), optimizing, managing and engaging activities.